2008
DOI: 10.1021/ja710156d
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Molecular Orientation Distributions and Electrochemical Kinetics in Subpopulations of an Immobilized Protein Film

Abstract: Charge transfer kinetics in immobilized, redox-active films have been studied using both cyclic voltammetry (CV) and electroreflectance (ER) techniques by other groups. 1,2 In these studies, rate constants obtained using ER techniques were higher than those determined from CV data, as observed here. This systematic difference can be explained by considering the following: Adsorption of a monolayer of molecules on a chemically and structurally heterogeneous electrode (e.g., indium-tin oxide) will generate a fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
(52 reference statements)
3
34
0
Order By: Relevance
“…The sensitivity can be enhanced by using an ATR geometry, wherein the probe beam is internally reflected multiple times through a planar waveguide electrode. 13,15,18,20 Compared with transmission and external reflection ER spectroscopy, PM-ATR spectroscopy provides a sensitivity enhancement of ten to several thousand, depending on the geometry of the waveguide electrode. The ATR geometry also provides spatial selectivity because the evanescent wave penetrates only a fraction of the wavelength (λ) into the medium adjacent to the waveguide.…”
Section: Theory Of Pm-atrmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity can be enhanced by using an ATR geometry, wherein the probe beam is internally reflected multiple times through a planar waveguide electrode. 13,15,18,20 Compared with transmission and external reflection ER spectroscopy, PM-ATR spectroscopy provides a sensitivity enhancement of ten to several thousand, depending on the geometry of the waveguide electrode. The ATR geometry also provides spatial selectivity because the evanescent wave penetrates only a fraction of the wavelength (λ) into the medium adjacent to the waveguide.…”
Section: Theory Of Pm-atrmentioning
confidence: 99%
“…1C). 15,18 This allows for the selective probing of molecules having absorbance transition dipoles aligned with the electric field vector of the evanescent wave. In an ensemble of molecules with a distribution of molecular orientations, the contribution of each molecule to the ER response is weighted by a factor of cos 2 α, where α is the angle between the electric field vector and the transition dipole of the molecule.…”
Section: Theory Of Pm-atrmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroelectrochemical techniques are particularly useful to mitigate those difficulties by focusing solely on the faradaic process and avoiding the strong non-faradaic electrical background. [10][11][12][13][14][15][16][17][18][19][20][21][22] Based on spectroscopic optical changes that typically accompany a redox event, it is usually possible to select the wavelength of a probing light beam to uniquely capture the optical changes associated with the faradaic process and is immune to the presence and motion of background ions in the electric double layer.…”
Section: Introductionmentioning
confidence: 99%
“…16 A common general trend from previous research suggested that the lower curvature of nanoparticle causes more perturbations of the protein structure, however that factor may not be universally true. 10,17,18 For instance, 2D self-assembled monolayers (SAM) of a polypepa) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%